Unfinished: a memoir - Jonas, Priyanka Chopra (Gurugram Penguin Random, 2021)
In this thoughtful and revealing memoir, readers will accompany one of the world's most recognizable women on her journey of self-discovery. A remarkable life story rooted in two different worlds, Unfinished offers insight into Priyanka Chopra Jonas's childhood in India.
Keywords: Motion picture actors and actresses; India